On Bending Response of Doubly Curved Laminated Composite Shells Using Hybrid Refined Models - Monge, JC (2019)
This paper presents a static analysis of laminated composite doubly-curved shells using refined kinematic models with polynomial and non-polynomial functions recently introduced in the literature. To be specific, Maclaurin, trigonometric, exponential and zig-zag functions are employed. The employed refined models are based on the equivalent single layer theories. A simply supported shell is subjected to different mechanical loads, specifically: bi-sinusoidal, uniform, patch, hydrostatic pressure and point load. The governing equations are derived from the Principle of Virtual displacement and solved via Navier-Type closed form solutions. The results are compared with results from Layer-wise solutions and different higher order shear deformation theories available. It is shown that refined models with non-polynomial terms are able to accurately predict the through-the-thickness displacement and stress distributions maintaining less computational effort compared to a Layer-wise models.